Isolation and Characterization of Phytase from Chicken Manure Bacteria - Irawan, Mega Pratiwi; Nurachman, Zeily (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
Cereals in animal feed contain anti-nutrients of phytic acid that has capability of chelating proteins and cations. Phytasecan be employed to reduce phytic acid through hydrolyzing phytic acid into free phosphate group and lower derivate ofinositol phosphate. The aim of the study was to isolate and characterize phytase obtained from chicken manure bacteria.The study included the screening of phytase-producing bacteria from chicken manure, the homology analysis of bacterium,and the determination of phytase activity. Phytase activity was measured from concentration of free phosphate. The resultsshowed that one phytase-producing isolate obtained from chicken manure grew in the medium containing 5% rice branextract at 37°C for 5 d. Based on a phylogeny is tree analysis of the genes related to 16S rRNA, the isolate was identified asAcinetobacter sp. TZ1. The extracellular phytase expressed by Acinetobacter sp. TZ1 exhibited optimum reactions at pH5 and 50°C. The enzyme showed activity of 64,6 nmol mL–1min–1 and specific activity of 236 nmol min–1mg–1. Relativemolecular mass of phytase TZ1 was 35 kDa. Phytase obtained is potential to improve animal feed quality by hydrolyzingphytic acid.